2023
DOI: 10.1021/jacs.3c02787
|View full text |Cite
|
Sign up to set email alerts
|

High-Concentration Self-Assembly of Zirconium- and Hafnium-Based Metal–Organic Materials

Abstract: Metal–organic frameworks (MOFs) are crystalline, porous solids constructed from organic linkers and inorganic nodes that are promising for applications in chemical separations, gas storage, and catalysis, among many others. However, a major roadblock to the widespread implementation of MOFs, including highly tunable and hydrolytically stable Zr- and Hf-based frameworks, is their benchtop-scalable synthesis, as MOFs are typically prepared under highly dilute (≤0.01 M) solvothermal conditions. This necessitates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 76 publications
(181 reference statements)
0
13
0
Order By: Relevance
“…Using either ZrCl 4 or ZrPiv as the node precursor at concentrations up to 1.0 M in DMF with stirring yields crystalline UiO-66 that is comparable in quality to the material prepared under the standard dilute conditions (Figure b). In particular, these high-concentration samples exhibit high Brunauer–Emmett–Teller (BET) surface areas of 1327 ± 8 and 1232 ± 7 m 2 /g for UiO-66–1.0 M (ZrCl 4 ) and UiO-66–1.0 M (ZrPiv), respectively …”
Section: High-concentration Solvothermal Synthesismentioning
confidence: 93%
See 3 more Smart Citations
“…Using either ZrCl 4 or ZrPiv as the node precursor at concentrations up to 1.0 M in DMF with stirring yields crystalline UiO-66 that is comparable in quality to the material prepared under the standard dilute conditions (Figure b). In particular, these high-concentration samples exhibit high Brunauer–Emmett–Teller (BET) surface areas of 1327 ± 8 and 1232 ± 7 m 2 /g for UiO-66–1.0 M (ZrCl 4 ) and UiO-66–1.0 M (ZrPiv), respectively …”
Section: High-concentration Solvothermal Synthesismentioning
confidence: 93%
“…An interesting question is why Zr-MOFs tend to form the same phase at low and high linker concentrations, , whereas M 2 (dobdc) materials undergo a phase transition to a new kinetic product at high reaction concentrations. , We propose that Zr- and Hf-MOFs are especially well-suited for high-concentration synthesis because their M 6 nodes are robust and well-defined and, thus, strongly direct linker coordination into specific structures, even at high concentrations. In contrast, the metal centers that form the backbone of M 2 (dobdc) materials can engage in many different coordination environments with the linkers during MOF self-assembly.…”
Section: High-concentration Solvothermal Synthesismentioning
confidence: 96%
See 2 more Smart Citations
“…In particular, the need for liters of solvent(s) and disproportionate quantities of acid modulators often limit MOF synthesis to subgram quantities. Recently, Matzger and co-workers, along with our group, found that much higher reaction concentrations (up to 1 M in some cases) can be used to produce high-quality MOFs with significantly reduced solvent waste. In a similar vein, we carried out a structure–property study to identify the optimal modulator for Zr-MOF synthesis, with the goal of reducing the amount of modulator required to produce highly crystalline material .…”
Section: User-friendly Mof Synthesismentioning
confidence: 99%